Keperluan elemen media dalam aplikasi Kosa Kata Bahasa Arab Mufradati pelajar UiTM / Muhamad Khairul Anuar Zulkepli ... [et al.] - Zulkepli, Muhamad Khairul Anuar; Abd Hamid, Mohd Zulkhairi; Wahab, Burhanuddin; Yahaya, Ahmad Fauzi; Mohamad, Norhayuza (2023)
Technology-based learning is a learning process that adapts elements or concepts of technology. It is growing in today's world of learning, especially Arabic vocabulary learning, which is diversified through many platforms and technologies such as applications, e-learning and others. The emergence of a prototype application can create a sense of interest and motivation towards learning Arabic vocabulary, especially at UiTM Kedah. This is because the mastery of the Arabic vocabulary of UiTM Kedah students has yet to reach the required level. To help those students, a creative or innovative idea needs to be contributed more by the current generation that is more technological. Thus, this study aims to analyse the needs of media elements in an Arabic vocabulary application to be developed at UiTM Kedah. This study is a quantitative study that adapts a questionnaire as the primary source of data. A total of 144 students who took the Arabic language subject code TAC401 (Introductory Arabic Part I) were made respondents. The collected data was analysed using SPSS version 28 software to measure respondents' needs. The study's findings show a high interpretation of the needs of media elements for the application that wants to be developed. The study's implication supports learning Arabic vocabulary through an application as a flexible learning aid that UiTM Kedah students can use.